Reproductive pathology of domestic mammals - McEntee, Kenneth (Academic Press, 1990)
This book evolved from a series of lectures and laboratories given by Dr. Kenneth McEntee to students at Cornell University, the University of Illinois, and Tufts University and is based on tissues from over 20,000 cases of reproductive disease in the International Registry of Reproductive Pathology, founded by Dr. McEntee. Dr. McEntee brings into sharp focus what is known of reproductive pathology in North America and abroad. His book will be an invaluable text and reference for those working on the diagnosis, prevention, and treatment of reproductive failures of all kinds. Key Features. The only comprehensive text on reproductive pathology of domestic mammals. Based on pathologic examination of more than 20,000 cases of reproductive disease. Covers clinical aspects of disease and associated lesions. Extensive reference list includes citations in twelve languages.